A line to kill : a novel - Horowitz, Anthony, 1955- (Harper, an imprint of HarperCollinsPublishers, 2021)
Invited to an exclusive literary festival on an island off the English coast, Hawthorne and Horowitz find themselves investigating a murder amidst a local feud over a disruptive power line.